Dinamika Keberhasilan Program Bertani Untuk Negeri di Kecamatan Gekbrong dalam Perspektif Persepsi dan Partisipasi - Natalia, Shelly; Arbi, Muhammad (Universitas Galuh, 2025)
The Bertani Untuk Negeri program is an agricultural empowerment initiative aimed at improving farming productivity, implementing standard operating procedures (SOP), and enhancing farmers’ welfare. Implemented in Gekbrong Subdistrict, Cianjur Regency, the program involves farmers as key actors. Its success depends largely on farmers' active participation and their perceptions of the program’s benefits and effectiveness. This study analyzes: (1) the influence of perceptions on farmer participation, (2) the influence of perceptions on program success, and (3) the influence of participation on program success. Conducted from February to June 2024, the study used a quantitative approach through surveys and questionnaires with 104 farmers from a population of 144. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Results show that farmers’ perceptions positively and significantly influence participation and program success. Participation has a stronger impact on program success and partially mediates the effect of perception. These findings highlight that positive perceptions and active farmer participation are critical for achieving program goals, including improving productivity, applying SOP, and increasing income.